2012
DOI: 10.1037/a0029213
|View full text |Cite
|
Sign up to set email alerts
|

Staying engaged during the week: The effect of off-job activities on next day work engagement.

Abstract: Although studies on employee recovery accumulate at a stunning pace, the commonly used theory (Effort-Recovery model) that explains how recovery occurs has not been explicitly tested. We aimed to unravel the recovery process by examining whether off-job activities enhance next morning vigor to the extent that they enable employees to relax and detach from work. In addition, we investigated whether adequate recovery also helps employees to work with more enthusiasm and vigor on the next workday. On five consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
318
1
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(356 citation statements)
references
References 53 publications
33
318
1
4
Order By: Relevance
“…The correlation is therefore not alarming to doubt the discriminate validity of pride. This confirms the theoretical assumption that PSM is a different concept from pride (Ten Brummelhuis & Bakker, 2012) …”
Section: Resultssupporting
confidence: 75%
“…The correlation is therefore not alarming to doubt the discriminate validity of pride. This confirms the theoretical assumption that PSM is a different concept from pride (Ten Brummelhuis & Bakker, 2012) …”
Section: Resultssupporting
confidence: 75%
“…This study sheds new light on previous findings by bringing new insight on why social activities may have been both effective (e.g., Mojza et al, 2010;Ten Brummelhuis & Bakker, 2012) and ineffective (Mojza et al, 2011;Sonnentag & Bayer, 2005) in reducing WPC and promoting resource recovery after work. Results from this study indicate that engaging in social activities does not divert internal reflection from work-related issues in individuals high in neuroticism.…”
Section: Discussionmentioning
confidence: 94%
“…However, studies have found conflicting evidence regarding the benefits of time spent on social activities (e.g., speaking with a friend on the phone). On the one hand, the amount of time spent on social activities during the evening and on the weekend has been positively related to workers' psychological detachment from work (e.g., Mojza, Lorenz, Sonnentag, & Binnewies, 2010;Ten Brummelhuis & Bakker, 2012). However, other studies have failed to confirm such benefits (Mojza, Sonnentag, & Bornemann, 2011;Sonnentag & Bayer, 2005).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations